Modelling Tourism Demand In Madeira Since 1946: And Historical Overview Based On A Time Series Approach - Oliveira, admin; de Almeida, António Manuel Martins (Journal of Tourism, Sustainability and Well-being, 2016)
Tourism is the leading economic sector in most islands and for that reason market trends are closely monitored due to the huge impacts of relatively minor changes in the demand patterns. An interesting line of research regarding the analysis of market trends concerns the examination of time series to get an historical overview of the data patterns. The modelling of demand patterns is obviously dependent on data availability, and the measurement of changes in demand patterns is quite often focused on a few decades. In this paper, we use long-term time-series data to analyse the evolution of the main markets in Madeira, by country of origin, in order to re-examine the Butler life cycle model, based on data available from 1946 onwards. This study is an opportunity to document the historical development of the industry in Madeira and to introduce the discussion about the rejuvenation of a mature destination. Tourism development in Madeira has experienced rapid growth until the late 90s, as one of the leading destinations in the European context. However, annual growth rates are not within acceptable ranges, which lead policy-makers and experts to recommend a thoughtfully assessment of the industry prospects.